APLIKASI PEMANTAUAN DAN PEMELIHARAAN BASE TRANSCEIVER STATION BERBASIS ANDROID - Farhan Subhan; Astriana Mulyani (LPPM Nusa Mandiri, 2017)
In the monitoring and maintenance of the Base Transceiver Station which runs today still manual, which all report results of monitoring and maintenance are reported through a single group chat application. If the owner of Base Transceiver Station has a little Base Transceiver Station, then report the results still could be known by the owner of Base Transceiver Station with fast and precise, but if the owner of Base Transceiver Station has many Base Transceiver Station, Base Transceiver Station owners will have difficulty knowing the results of the report quick and precise. With the problems, it is made program-based mobile device applications that can be implemented to monitor and maintain the Base Transceiver Station. The device used in the manufacture of these applications require minimal android 4.2.2 OS system, the screen has a minimum of 4